(e,2e) Ionization of helium and the hydrogen molecule: Signature of two-centre interference effects - Casagrande, S.; Naga, A.; Mezdari, F.; Lahmam-Bennani, A.; Bolognesi, P.; Joulakian, B.; Chuluunbaatar, O.; Al-Hagan, O.; Madison, D.; Fursa, Dmitry; Bray, Igor (IOP Publishing Ltd, 2008)
Relative (e,2e) triply differential cross sections (TDCS) are measured for the ionization of the helium atom and the hydrogen molecule in coplanar asymmetric geometry at a scattered electron energy of 500 eV and ejected electron energies of 205, 74 and 37 eV. The He experimental results are found to be in very good agreement with convergent close-coupling calculations (CCC). The H2 experimental results are compared with two state-of-the-art available theoretical models for treating differential electron impact ionization of molecules. Both models yield an overall good agreement with experiments, except for some intensity deviations in the recoil region. Similar (e,2e) works were recently published on H2 with contrasted conclusions to the hypothesis that the two H nuclei could give rise to an interference pattern in the TDCS structure. Murray (2005 J. Phys. B: At. Mol. Opt. Phys. 38 1999) found no evidence for such an effect, whereas Milne-Brownlie et al (2006 Phys. Rev. Lett. 96 233201) reported its indirect observation. In this work, based on a direct comparison between experimental results for He and H2, we observe an oscillatory pattern due to these interference effects, and for the first time the destructive or constructive character of the interference is observed, depending on the de Broglie wavelength of the ejected electron wave. The experimental finding is in good agreement with the theoretical prediction by Stia et al (2003 J. Phys. B: At. Mol. Opt. Phys. 36 L257).